Urgency of Suspect Determining In the Investigation Process on Human Rights Perspective - Suwarno Suwarno; Sri Endah Wahyuningsih (Universitas Islam Sultan Agung, 2020)
Protection of suspect rights related to human rights protection. In the Criminal Procedure Code Investigators are given the authority for forced attempts in the form of arrest, detention, confiscation and so on. If a person is named a suspect, he is confronted by the investigator whose job it is to find, collect evidence about the criminal act that occurred. The purpose of this study 1. To analyze the determination of suspects 2. To analyze the obstacles faced by law enforcers and their solutions. The research methods used are 1. Approach method 2. Type or research specifications 3. Types of data and data sources 4. Data collection methods 5. Data analysis methods. And the conclusions in this study are 1. The implementation of the determination of the suspect, that the legality of the determination of the suspect in the investigation process can be recognized if the rights of the suspect are fulfilled. a. The investigator can only determine the status of a suspect after the results of the investigation have obtained sufficient initial evidence of at least 2 (two) types of evidence. b. to determine sufficient preliminary evidence by means of a case title. 2. Constraints faced by law enforcers related to the determination of suspects and the solutions are a. suspects often provide complicated statements in front of investigators and removing evidence will take time to reveal the criminal acts committed. b. the summons of witnesses, victims and experts are often not on time c. Lack of budget support. The solution to these constraints is a. in the future, operational funds for witnesses who are summoned are needed to provide information so as to facilitate the investigation process. b. the need for regulations that limit the length of time a person has the status of a suspect to avoid potential human rights violations and to provide legal certainty for justice seekers.